2020
DOI: 10.3389/fmicb.2020.01941
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus johnsonii BS15 Prevents Psychological Stress–Induced Memory Dysfunction in Mice by Modulating the Gut–Brain Axis

Abstract: Researchers are attempting to harness the advantages of the gut–brain axis to prevent neurocognitive disorders by enhancing intestinal health. In this study, four groups of ICR mice were orally gavaged with either phosphate-buffered saline (control and CW groups) or the probiotic strain Lactobacillus johnsonii BS15 (P and PW group; daily amounts of 2 × 10 8 colony-forming units) for 28 days. From days 22 to 28, the mice in the CW and PW groups were subjected to wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 66 publications
3
17
0
Order By: Relevance
“…The impact of the gut microbiome can extend past neurological conditions to capacity and behavioral outcomes. Specifically, a recent study showed that FMT rescued bacterial and behavioral changes after TBI (Wang et al, 2020). As expected, we found that the microbiota of AD mice transplanted into young mice after TBI produced motor deficits (Figure 3d).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The impact of the gut microbiome can extend past neurological conditions to capacity and behavioral outcomes. Specifically, a recent study showed that FMT rescued bacterial and behavioral changes after TBI (Wang et al, 2020). As expected, we found that the microbiota of AD mice transplanted into young mice after TBI produced motor deficits (Figure 3d).…”
Section: Discussionsupporting
confidence: 86%
“…Our current results show a trend wherein the levels of Lactobacillus johnsonii are decreased in FMT-AD animals compared to their FMT-young counterparts (Figure 2c). These results are further supported by a recent study that shows probiotics increased various Lactobacillus, including specifically the Lactobacillus johnsonii species, which prevented intestinal permeability, modulated proinflammatory factors, and correlated with better behavioral results (Wang et al, 2020). Other studies have shown that probiotics may increase the gut microbiome diversity and increase the abundance of Bacteroides and Faecalibacterium (Liu et al, 2020a).…”
Section: Discussionsupporting
confidence: 65%
“…4 c). Several beneficial functions of L. johnsonii have been reported, including thickened mucous membranes in stomach ulcers [ 30 ], restored numbers of serum IgA, IgG, and CD8 + cells, increased splenocyte counts in aged mice with protein–energy malnutrition [ 31 ], decreased glucagon and glucose levels in diabetic rats [ 32 ], and prevention of memory dysfunction [ 33 ]. The proportion of gut Akkermansia was also significantly elevated, to 0.41%, in mice receiving probiotics (high-dose) plus postbiotics, whereas in the 16-month-old mice it was only 0.04% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Ct values normalized with β-actin were used to calculate the mRNA-expression levels of brain-derived neurotrophic factor (BDNF), cyclic amp response element-binding protein (CREB), and the stem cell factor (SCF). Primers used in the RT-qPCR reactions were previously described [ 37 ] and are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%